A ROMAN COPY OF THE "WESTMACOTT EPHEBE" TYPE FROM TEMENOUTHYRAI IN PHRYGIA - Dinç, Münteha; Taştemür, Emre (Mersin University, 2026)
This article presents a new example from Asia Minor of Polykleitos' famous athlete statues, which can mostly be traced through Roman-period copies. The statue, depicting a naked young man standing upright, was found in 2000 during a foundation excavation in the city center of Uşak province. The study first provides a detailed description of the statue and then discusses its typology and iconography. The statue, understood to be a copy of the Westmacott Epheb type, is thought to have been produced between the last quarter of the 1st century AD and the first half of the 2nd century AD, possibly for decorative use in an important public building (a Roman bath or theater) or in the house of an elite Roman based on similar examples. The Temenouthyrai copy stands out as the only known findspot copy from Asia Minor, apart from the Aphrodisias head and the Tarsus example (only a variant). With this study, the statue in question takes its place as a qualified example among the copies of the Westmacott Epheb type that have survived to the present day. This statue is a very close example of a model known for its dimensions and artistic craftsmanship, contributing greatly to the level of sophistication of the art of sculpture in the Roman province of Asia.

Bu makalede, Polykleitos’un çoğunlukla Roma Dönemi kopyaları üzerinden takip edilebilen ünlü sporcu heykellerine Anadolu’dan yeni bir örnek sunulmaktadır. Çıplak ve ayakta duran genç bir erkeği tasvir eden heykel, 2000 yılında Uşak ili kent merkezindeki bir temel kazısı sırasında bulunmuştur. Çalışmada öncelikle heykelin detaylı bir tanımı yapılmakta sonrasında ise tipolojisi ve ikonorafisi üzerinden bir değerlendirme sunulmaktadır. Nitekim Westmacott Epheb tipinde bir kopya eser olduğu anlaşılan heykelin benzer örneklerden de yola çıkılarak olasılıkla antik kentin önemli bir kamu yapısında (bir Roma Hamamı ve ya tiyatro) ya da elit bir Romalının evinde dekoratif amaçlı kullanılmak üzere MS 1. yüzyılın son çeyreği ile MS 2. yüzyılın ilk yarısı arasında üretilmiş olduğu düşünülmektedir. Temenouthyrai kopyası, Aphrodisias başı ve Tarsus örneği (sadece bir varyant) dışında Anadolu’dan buluntu yeri bilinen tek kopya olması özelliği ile ön plana çıkmaktadır. Bu çalışma ile söz konusu heykel, Westmacott Epheb tipinin günümüze ulaşan kopyaları arasında nitelikli bir örnek olarak yerini almaktadır. Söz konusu heykel, ölçüleri ve sanatsal işçiliği ile bilinen bir modelin çok yakın bir örneği olup Roma’nın Asya Eyaletindeki heykeltıraşlık sanatının gelişmişlik düzeyine büyük bir katkı sunmaktadır.
Phrygia’daki Temenouthyrai’den “Westmacott Epheb” Tipinde Bir Roma Kopyası
Keywords: Archaeological Science; Arkeoloji Bilimi